Deletion of Kvβ1.1 subunit leads to electrical and haemodynamic changes causing cardiac hypertrophy in female murine hearts. Issue 4 (25th February 2016) - Tur, Jared; Chapalamadugu, Kalyan C.; Padawer, Timothy; Badole, Sachin L.; Kilfoil, Peter J.; Bhatnagar, Aruni; Tipparaju, Srinivas M.
Abstract : New Findings: What is the central question of this study? The goal of this study was to evaluate sex differences and the role of the potassium channel β1 (Kvβ1) subunit in the heart. What is the main finding and its importance? Genetic ablation of Kvβ1.1 in females led to cardiac hypertrophy characterized by increased heart size, prolonged monophasic action potentials, elevated blood pressure and increased myosin heavy chain α (MHCα) expression. In contrast, male mice showed only electrical changes. Kvβ1.1 binds the MHCα isoform at the protein level, and small interfering RNA targeted knockdown of Kvβ1.1 upregulated MHCα. Cardiovascular disease is the leading cause of death and debility in women in the USA, and cardiac arrhythmias are a major concern. Voltage‐gated potassium (Kv) channels along with the binding partners; Kvβ subunits are major regulators of the action potential (AP) shape and duration (APD). The regulation of Kv channels by the Kvβ1 subunit is unknown in female hearts. In the present study, we hypothesized that the Kvβ1 subunit is an important regulator of female cardiac physiology. To test this hypothesis, we ablated (knocked out; KO) the KCNAB1 isoform 1 (Kvβ1.1) subunit in mice and evaluated cardiac function and electrical activity by using ECG, monophasic action potential recordings and echocardiography. Our results showed that the female Kvβ1.1 KO mice developed cardiac hypertrophy, and the hearts were structurally different, with enlargement and increased area. The electrical derangements caused by Kvβ1.1 KO in female mice included long QTc and QRS intervals along with increased APD (APD20–90% repolarization). The male Kvβ1.1 KO mice did not develop cardiac hypertrophy, but they showed long QTc and prolonged APD. Molecular analysis showed that several genes that support cardiac hypertrophy were significantly altered in Kvβ1.1 KO female hearts. In particular, myosin heavy chain α expression was significantly elevated in Kvβ1.1 KO mouse heart. Using a small interfering RNA strategy, we identified that knockdown of Kvβ1 increases myosin heavy chain α expression in H9C2 cells. Collectively, changes in molecular and cell signalling pathways clearly point towards a distinct electrical and structural remodelling consistent with cardiac hypertrophy in the Kvβ1.1 KO female mice. Abstract :